Necrotizing fasciitis: 11‐year retrospective case review in South Auckland. Issue 10 (24th July 2015) - Kulasegaran, Suheelan; Cribb, Benjamin; Vandal, Alain C.; McBride, Stephen; Holland, David; MacCormick, Andrew D.
Abstract: Background: The aims of this paper were to review our experience with necrotizing fasciitis at Middlemore Hospital and to define the trends in incidence, inpatient mortality and microbiological profile. Methods: A computerized search of the electronic medical records was undertaken to identify adult patients with a diagnosis of necrotizing fasciitis between January 2000 and December 2010. A retrospective review of the clinical records was performed. Results: Of the 138 patients with necrotizing fasciitis identified, 129 had their diagnosis confirmed at operation. The mortality at 30 days was 20.3% (95% confidence interval (CI) 13.9%–28.0%). There was a significant reduction in hospital mortality in each successive year of the study period with an odds ratio of 0.84 (95% CI 0.71–0.98, P = 0.03). A pattern of increasing incidence was noted until February 2004 (95% CI September 2002–July 2005). This was followed by a significant decrease in incidence. The empirical antibiotic regime of clindamycin, gentamicin and penicillin provides satisfactory cover against 95% of the causative pathogens. Conclusion: This represents the largest single‐centre published case series in New Zealand. Despite concerns of increasing incidence and mortality associated with necrotizing fasciitis in New Zealand, the experience in South Auckland shows a decrease in incidence of necrotizing fasciitis since 2004 and a statistically significant decreasing trend in hospital mortality.